Tinjauan Brand Monitoring terhadap Pemberitaan Motor Listrik Brand Alva - Rachel Nasywa Aurelia (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The development of the automotive industry continues to grow rapidly and has modifications. The Alva One company is famous for producing electric motorbikes with one of the launches of its newest electric motorbike called Alva One XP. The popularity of Alva One brand products has encouraged the implementation of product monitoring or brand monitoring from news reports via the website. This research aims to see the level of positive sentiment, mentions and reach of the most influential websites. The research method was carried out by quantitative descriptive analysis and using a positivsm approach. Data collection is assisted by Brand24 application tools which focus on news website media. The research results illustrate the extent of positive sentiment received, the number of mentions and reach of the websites that have the most influence on reporting on the Alva One brand.